Impact of the COVID-19 pandemic on patients with coronary artery disease requiring cardiac surgery at a German university hospital - Jan S. Englbrecht; Jan K. Landwehrt; Henryk Welp; Sven Martens; Antje Gottschalk (Journal of Cardiothoracic Surgery)
Abstract Background Studies show conflicting results regarding the impact of the COVID-19 pandemic on the treatment of patients with coronary artery disease requiring cardiac surgery and data from Germany are lacking. In this study, two patient cohorts who underwent coronary artery bypass graft surgery before and after the start of the COVID-19 pandemic were compared. Methods Patients who presented for coronary artery bypass graft surgery before (01.05.18–30.04.19; group “B”) or during the COVID-19 pandemic (01.05.20-30.04.21; group “P”) at the University Hospital Münster in Germany were retrospectively identified and compared regarding demographics, preoperative status, surgical data, and postoperative outcome. Results 513 (group “B”) and 501 patients (group “P”) were included, demographics were comparable. In group “P”, preoperative myocardial infarction and emergency indications were more frequent, heart-lung machine and aortic clamping times were longer. Postoperative ICU-days and inpatient stay did not differ. Postoperative need of an extracorporeal life support system and intrahospital mortality tended to be higher in group “P”, without reaching statistical significance. Conclusion The COVID-19 pandemic had a significant impact on cardiac surgical care with the prioritization of emergency procedures. Patients treated during the pandemic were in a more critical preoperative condition, duration of surgery was longer, but post-operative mortality was comparable.